2018
DOI: 10.3390/su10124487
|View full text |Cite
|
Sign up to set email alerts
|

Well-to-Wheels Approach for the Environmental Impact Assessment of Road Freight Services

Abstract: The diffuse nature of road transport and the heterogeneity of heavy vehicles have hindered the implementation of emissions accounting systems. Even though there are emission factors in well-known databases, these factors have commonly been designed in industrialized countries, which might have geography, type of roads, and operating conditions different to other countries. This paper proposes a method for the energy consumption and emissions estimation based on vehicle operating conditions in regions with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The growing fuel consumption and carbon emissions from such heavy-duty equipment add to the already existing emissions in the transport and logistics sector [2,8]. For example, without the intervention of governments and clear energy efficiency measures it is predicted that in the European Union greenhouse gas emissions produced by trucks will be around 35% higher in 2030 than the 1990 levels [9]. In comparison to other vehicles, diesel vehicles consume the most fuel [2,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing fuel consumption and carbon emissions from such heavy-duty equipment add to the already existing emissions in the transport and logistics sector [2,8]. For example, without the intervention of governments and clear energy efficiency measures it is predicted that in the European Union greenhouse gas emissions produced by trucks will be around 35% higher in 2030 than the 1990 levels [9]. In comparison to other vehicles, diesel vehicles consume the most fuel [2,10].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, heavy-duty vehicles are being overloaded in order to reduce operating costs, and this has had significant negative environmental impacts [3]. Thus, because fuel efficiency is directly linked to CO 2 emission [9], vehicle fuel consumption and vehicle productivity [1] should be explicitly considered together in order to reduce these vehicles' environmental impact.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the calculation and analysis of the transport sector's carbon footprint, as well as the carbon footprint of the different transport modes comprised by it, are critical in planning and implementing initiatives and policies to reduce greenhouse gas emissions affecting climate change. Thus, many studies on carbon footprint calculation in the transport sector can be found in the recent scientific literature [27][28][29][30][31].…”
mentioning
confidence: 99%
“…With the rapid growth of freight turnover light and heavy truck transportation activities increases, and the energy consumption is mainly diesel. Diesel consumption is related to vehicle control technology, road slope and load factor [51]. In the GB1589 new national standard, the upper limit of truck weight is large, so the increase of diesel input-output structure leads to the increase of CO 2 emissions.…”
Section: Energy Input and Output Factor Analysismentioning
confidence: 99%